2015
DOI: 10.1016/j.vaccine.2015.06.068
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric immunization-related safety incidents in primary care: A mixed methods analysis of a national database

Abstract: BackgroundChildren are scheduled to receive 18–20 immunizations before their 18th birthday in England and Wales; this approximates to 13 million vaccines administered per annum. Each immunization represents a potential opportunity for immunization-related error and effective immunization is imperative to maintain the public health benefit from immunization. Using data from a national reporting system, this study aimed to characterize pediatric immunization-related safety incident reports from primary care in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
(48 reference statements)
1
39
0
Order By: Relevance
“…5 Research and improvement efforts may now mitigate harm occurring during the vaccination process, which commonly include: giving the wrong vaccine; giving vaccines at the wrong time in a schedule; giving extra (unnecessary) vaccines; administering vaccines via the wrong route; and prescribing or administering the wrong dose. 2,6,7 Several studies have shown that approximately one-third of patients experience at least one vaccine error. 8,9 Feikema and colleagues estimated the United States wastes $26.5 million per annum on unnecessary vaccines given to infants between 19 and 35 months.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 Research and improvement efforts may now mitigate harm occurring during the vaccination process, which commonly include: giving the wrong vaccine; giving vaccines at the wrong time in a schedule; giving extra (unnecessary) vaccines; administering vaccines via the wrong route; and prescribing or administering the wrong dose. 2,6,7 Several studies have shown that approximately one-third of patients experience at least one vaccine error. 8,9 Feikema and colleagues estimated the United States wastes $26.5 million per annum on unnecessary vaccines given to infants between 19 and 35 months.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Surveillance systems primarily capturing data about adverse drug reactions, such as the Vaccine Adverse Event Reporting System, can also contain reports about the vaccine delivery process. 11 Whilst safety incident reporting systems cannot accurately measure the frequency of vaccination errors, they can support the identification of priorities for improvement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is, however, an opportunity to target specific discipline or professional groups to stimulate a culture of reporting, and efforts in anaesthetics have been commendable. From our analysis of incidents involving children in primary care3 4 we would advocate initiatives that promote reporting across multiple sectors, not least patient-reporting, at local and national levels. Further, encouraging reports about specific safety incident types and specific patient groups (eg, delays in treatment received by socially deprived children) would support capture of a diverse range of issues underpinning the most common or most important problems for those patients.…”
mentioning
confidence: 99%